Pomoc publiczna w kreowaniu rozwoju lokalnego - szanse i bariery - Filipiak, Beata (State aid in creating the local development - chances and barriers, 2006)
The article presents problems of state aid. The author analyzes state aid as a tool, which is used for creating and supporting local development. The paper presents possible factors for use of this instrument for creating local development, which are included in EU law and Polish law. In the end of article, the chances and barriers of using this instrument by self-governments, are discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 342-355